Advances and challenges in regenerative therapies for abdominal aortic aneurysm - Chao, Calvin L.; Applewhite, Brandon; Reddy, Nidhi K.; Matiuto, Natalia; Dang, Caitlyn; Jiang, Bin (Frontiers in Cardiovascular Medicine, 2024)
Abdominal aortic aneurysm (AAA) is a significant source of mortality worldwide and carries a mortality of greater than 80% after rupture. Despite extensive efforts to develop pharmacological treatments, there is currently no effective agent to prevent aneurysm growth and rupture. Current treatment paradigms only rely on the identification and surveillance of small aneurysms, prior to ultimate open surgical or endovascular repair. Recently, regenerative therapies have emerged as promising avenues to address the degenerative changes observed in AAA. This review briefly outlines current clinical management principles, characteristics, and pharmaceutical targets of AAA. Subsequently, a thorough discussion of regenerative approaches is provided. These include cellular approaches (vascular smooth muscle cells, endothelial cells, and mesenchymal stem cells) as well as the delivery of therapeutic molecules, gene therapies, and regenerative biomaterials. Lastly, additional barriers and considerations for clinical translation are provided. In conclusion, regenerative approaches hold significant promise for in situ reversal of tissue damages in AAA, necessitating sustained research and innovation to achieve successful and translatable therapies in a new era in AAA management.